Analysis of Mediation as an Alternative Resolution of Medical Disputes Based on Supreme Court Regulation Number 1 of 2016 - Puji Yati (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2026)
The increase in medical disputes in Indonesia occurs along with the development of health services and increasing public legal awareness. Dispute resolution through litigation is often considered ineffective because it takes a long time, is expensive, and creates a confrontational relationship between medical personnel and patients. Therefore, mediation is present as an alternative dispute resolution that prioritizes deliberation, communication, and mutual agreement. This study aims to analyze the regulation, implementation, and effectiveness of mediation as an alternative resolution of medical disputes based on Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court. The research method used is normative legal research with a statutory, conceptual, and case approach. Data were obtained through literature and document studies, then analyzed descriptively qualitatively. The results of the study indicate that mediation has a strong legal basis and provides various advantages, such as a faster resolution process, lower costs, maintaining confidentiality, and being able to maintain good relationships between medical personnel and patients. However, the implementation of mediation still faces obstacles such as low public understanding, limited mediators who have competence in the health sector, and a legal culture that still tends to be litigative. Therefore, optimization is needed through improving mediator competence, strengthening public legal awareness, and maximizing mediation implementation to achieve fair, effective, and humane dispute resolution.